The morphology of the cibarial armature and sensilla of Mansonia titillans, Psorophora cingulata, Coquillettidia arribalzagae, Culex coronator and Limatus durhamii (Diptera: Culicidae) - Sandra Boza; Mario Vargas (Revista de Biología Tropical, 2006)
A detailed description of the cibarial armature of the Neotropical mosquitoes Mansonia titillans, Psorophora cingulata, Coquillettidia arribalzagae, Culex coronator and Limatus durhamii, is presented. A sample of 15 specimens of each species was taken from the collections of two mosquito ecological projects located at Santa Clara, San Carlos, Alajuela and from La Selva, Sarapiquí, Heredia, Costa Rica. Each specimen, preserved in alcohol, was cleared, put into a mounting medium, head separated from body and eyes pinched to expose the cibarial armature and sense organs; finally a coverslip was added for a permanent slide. The bodies of all the mosquitoes were also mounted onto slides. The descriptions of the cibarial armatures were based on the characteristics of the dome, body, transversal bar, lateral flanges and cibarial teeth. Also the number, distribution and type of the sense organs are given. From the analysis, and comparison with known descriptions of other neotropical species, we conclude that the five species studied show enough characteristics for species recognition purposes. Rev. Biol. Trop. 54 (3): 815-820. Epub 2006 Sept. 29. Se presenta una detallada descripción de la armadura cibarial y órganos sensoriales de hembras de mosquitos de cinco especies neotropicales, Mansonia titillans, Psorophora cingulata, Coquillettidia arribalzagae, Culex coronator y Limatus durhamii. Se tomó una muestra de 15 especimenes de cada especie de las colecciones de mosquitos de dos proyectos ecológicos localizados en Santa Clara, San Carlos, Alajuela y de La Selva, Sarapiquí, Heredia, Costa Rica. Los especimenes, preservados en alcohol de 85°, se aclararon en solución de Nesbitt, se disecaron las cabezas y se punzó los ojos compuestos para exponer la armadura cibarial y sus órganos sensoriales. Se utilizó el medio de Hoyer para hacer las preparaciones fijas. Asimismo los cuerpos de los especimenes fueron colocados en el medio de montaje. A todas las preparaciones se les colocó un cubreobjeto. Se utilizó la microscopia de contraste de fases para lograr una mejor apreciación de las estructuras. La descripción de las armaduras cibariales se basó en las características del domo, cuerpo, barra transversal y barras laterales, y dientes cibariales. También se informa el número, distribución y tipo de los órganos sensoriales. Hay diferencias estructurales suficientes para distinguir las cinco especies estudiadas entre sí y de otras especies de la culicidofauna neotropical.